Trust-A Catalyst to Knowledge Transfer: Contemporary Studies - Hasnain, Sheikh Shamim (Advances in Social Sciences Research Journal, 2017)
This is a literature based paper addressing the contemporary studies on the impacts of trust on knowledge transfer. Knowledge transfer is one of the important elements of knowledge management process. Knowledge transfer helps organisations achieve competitive advantages and organisations may formulate new strategies to adjust themselves with the dynamic business environments. Trust works as a lubricant between the knowledge transfers and the knowledge recipients. It is unfortunate to note that many knowledge management gurus have ignored to study this catalyst’s influences on knowledge transfer. This paper has made an endeavour to assemble the vital studies on these issues. Future researchers may empirically study the impact of trust on knowledge transfer in numerous contexts with a view to redressing the huge gray areas on these issues.